Evaluating the usefulness and ease of use of e-learning platforms for enhancing training effectiveness among civil servants in Suruhanjaya Perkhidmatan Awam Malaysia: a pilot study - Abdullah Thani, Ayu Kamareenna; Amran, Atiela; Azhari, Nurul Nadhira Amalin; Alias, Noor Rahmawati; Rosely, Nurhidayah (Penerbit UiTM (UiTM Press), 2025)
In today’s rapidly changing digital landscape, e-learning has become crucial for enhancing the skills and capabilities of government servants. This pilot study examines how public servants at Suruhanjaya Perkhidmatan Awam Malaysia, Putrajaya, perceive the utility and convenience of using e-learning platforms, as well as how these perceptions impact the success of training and development programs. The study, which followed the Technology Acceptance Model (TAM), included 30 volunteers from diverse departments to test the reliability and validity of the suggested measuring scales. Data were collected using a structured survey and analysed using SPSS, with Cronbach’s alpha values exceeding 0.70 for all constructs, indicating strong internal consistency. The findings provide preliminary justification for conducting a larger study and shed light on the significance of e-learning in the professional growth of civil officials. Finally, this research can help policymakers and HR departments improve the design and delivery of e-learning projects in the public sector